COMPARISON BETWEEN GEMCITABINE-CARBOPLATIN AND COMBINATION OF GEMCITABINE-CARBOPLATIN AND CELECOXIB IN UROTHELIAL CARCINOMA CELL APOPTOSIS - Pratama, Widya Sakti; Soetojo, Soetojo; Hakim, Lukman (Indonesian Journal of Urology, 2019)
Objective: To determine the combination effect of celecoxib and gemcitabine-carboplatin chemotherapy to the apoptosis of cultured-urothelial cancer cell line. Material & Methods: Urothelial carcinoma cell line originating from Bladder Ca 5637 was cultured and used in this in vitro study. Three-groups of cultured-urothelial cancer cell line consisted of (1) control (C), (2) gemcitabine-carboplatin treated group (GC) and (3) gemcitabine-carboplatin and celecoxib treated group (GCC) were treated with 0.086 µM gemcitabine, 290 µM carboplatin and 25 µM celecoxib. All groups were evaluated at 24 hours following treatment, and the apoptotic index (AI) measured accordingly. Results: Significant mean apoptotic index differences were found between the C and GC group; and between C and GCC groups at 24 hours following treatment. However, the AI of GCC was lower than the GC group although not statistically significant (p>0.05). Conclusion: Our study have shown that gemcitabine-carboplatin and the combination of both with celecoxib may increase the apoptosis of urothelial cancer cell line. The role of celecoxib in the addition of gemcitabine-carboplatin to treat urothelial cancer cell line needs to be elucidated further.